Exploring the Moderating Role of Gender in Juvenile Hacking Behaviors - Holt, Thomas J. (Crime & delinquency, 2020)
Criminological research has demonstrated the significant relationship between deviant peer associations, a lack of self-control, and individual delinquency. These relationships also account for involvement in cybercrime, though these results are based largely on adult samples. There is less research considering juvenile offending online, particularly examining involvement in property-based offenses such as computer hacking. This study utilized an international sample of 48,327 juvenile respondents in the Second International Self-Report of Delinquency (ISRD-2) study to examine the role of gender as a moderating factor in the relationship between deviant peer associations, self-control, opportunity, and self-reported computer hacking behavior. The findings demonstrated different correlates associated with hacking for males and females, as well as differences on the basis of urban and rural residency.